Examining self-concept development in early adolescence via the true intraindividual change models - Buško, Vesna; Marušić Štimac, Orjana (2006)
Latent state-trait theory (LST ; e.g. Steyer et al., 1992, 1999 ; Deinzer et al., 1995) as an extension of the classical psychometric test theory was developed based on a key notion that the measurement of any psychological attribute is shaped not only by stable individual or trait component but also by systematic albeit unstable situation-related influences. Following the assumptions of the LST theory, Steyer et al. (1997, 2000 ; 2004) introduced the particular class of structural equation models, where the true intraindividual change scores between successive occasions of measurement correspond to the values of endogenous latent variables. Various substantive hypotheses on the correlates and predictors of true change between the measurements can further be tested by such a model specification. Using the true change modeling procedures, intraindividual variations in self-report measures of specific domains of perceived self-competence were studied in a sample of 312 preadolescents on three and four occasions within a two year period. The models of LST theory were specified to include the latent variables corresponding to the state variability as well as the trait change in self-competence scores. The tested structural equation models and the parameters obtained point to different patterns of relationships of latent state and latent change perceived self-competence measures with particular antecedent and achievement variables.
Projekt MZOS
ENG